The Role of Learning Management Systems in Malaysian Universities: Advancing Quality Education and Reducing Inequalities - Kenneth, Baayeh; Francis, Amoako; Asha, Alam; Siti Nurbaayah, Daud; Ida, Hindarsah; Khan Sarfaraz, Ali (INTI International University, 2025)
The successful use of Learning Management Systems (LMS) in higher education institutions is critical to improving the quality of teaching and encouraging student engagement. The paper presents trends, tendencies, and challenges of LMS use among Malaysian public and private university teachers. Employing a quantitative method, the research carried out surveys of teaching staff from different disciplines. The findings show stark contrasts between private and public institutions regarding LMS infrastructure, instructor preparedness, and pedagogical integration. By resolving these differences, LMS can provide an equitable digital learning environment in Malaysia by increasing access to high-quality education (SDG 4) and decreasing gaps between public and private schools or between urban and rural students (SDG 10). Private universities show high adoption rates, whereas public universities are held back by infrastructural and bureaucratic problems. The study provides recommendations to bridge the gaps and advance the digital teaching environment in Malaysian higher education.